Delayed percutaneous endoscopic gastrostomy tube removal in patients with oropharyngeal carcinoma - John T Lucas; Rita Poon; Scott Finlay; Ryan Anderson; Mac Robinson; Ralph D'Agostino; Kathryn M Greven; Mercedes Porosnicu (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Objective: Early nutritional intervention through enteral feeding can reduce treatment alterations and complications in patients with Oropharyngeal Cancer (OPC) undergoing Chemoradiation Treatment (CRT). There is no conclusive evidence supporting prophylactic (pPEG) versus reactive PEG. Prolonged PEG dependence is a concerning adverse effect of pPEG. Recognition of risk factors for pPEG can trigger early interventions to prevent prolonged dependence. This study aims to identify the risk factors for prolonged pPEG dependence in a sample of oropharyngeal cancer patient population treated with concurrent chemoradiotherapy at our institution.   Methods:  This is a retrospective analysis of 75 OPC patients with definitive CRT and pPEG tube placement at our institution. The relationships between potential predictors and time to pPEG tube removal were evaluated using Cox proportional hazards univariate and multivariate modeling.  Results: Prophylactic PEG tube use at one year was 15.1% based on estimates from the Kaplan-Meier curve. After adjusting for patient- and treatment- factors, mucositis grade and advanced cancer stage remained significant predictors of delayed pPEG tube removal in the multivariate model. Conclusion: High grade mucositis, tumor location, and advanced cancer stage contribute to delayed pPEG tube removal, but these characteristics may also place patients at highest risk for reactive PEG tube placement.  Although this study is limited in size and design, it describes the characteristics of a population with pPEG placement, as well as factors for delayed PEG tube removal.